Modelling of riverine flooding using HEC-RAS - a case study of Badri Khawar River in KPK, Pakistan - Saqib Ehsan,; Qazi Muhammad Yasir,; Rana Muhammad Awais,; Talha Sattar,; Ghulam Mustafa,; Usama Fida, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Floods are one of the most occurring disasters in the world. Pakistan gets affected by flooding due to its diverse geography and has to lose several lives of people every year. The main objective of this study was to carry out modeling of riverine flooding using HEC-RAS program to estimate the safe channel capacity of the project reach and identify the vulnerable areas along the project reach for different flooding scenarios. A 9.21 Km long reach of Badri Khawar river, a right bank tributary of Indus River in KPK province has been taken as a case study. Based on the available data, one dimensional steady flow analysis in HEC-RAS has been carried out for different flooding scenarios. By analyzing the simulated results, the safe channel capacity of the study reach was found to be in the range of 125m3 /s to 100m3 /s from upstream to downstream. Based on the extent of flooding in different scenarios, vulnerable areas have been delineated on a flood map devised by the help of Google Earth. There is more inundation at the left overbank as compared to the right overbank. For the worst-case scenario, the maximum estimated flood extension on left bank side was about 425m while on the right bank side it was 204m. Based on the results of this research, it is suggested to enhance the existing flood protection measures along the project reach and improve the flood warning system and emergency evacuation mechanism in the vulnerable areas for long-term flood safety.